5(x-7)+(4x+2)=(5x-4)-2(x+5)

Simple and best practice solution for 5(x-7)+(4x+2)=(5x-4)-2(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-7)+(4x+2)=(5x-4)-2(x+5) equation:


Simplifying
5(x + -7) + (4x + 2) = (5x + -4) + -2(x + 5)

Reorder the terms:
5(-7 + x) + (4x + 2) = (5x + -4) + -2(x + 5)
(-7 * 5 + x * 5) + (4x + 2) = (5x + -4) + -2(x + 5)
(-35 + 5x) + (4x + 2) = (5x + -4) + -2(x + 5)

Reorder the terms:
-35 + 5x + (2 + 4x) = (5x + -4) + -2(x + 5)

Remove parenthesis around (2 + 4x)
-35 + 5x + 2 + 4x = (5x + -4) + -2(x + 5)

Reorder the terms:
-35 + 2 + 5x + 4x = (5x + -4) + -2(x + 5)

Combine like terms: -35 + 2 = -33
-33 + 5x + 4x = (5x + -4) + -2(x + 5)

Combine like terms: 5x + 4x = 9x
-33 + 9x = (5x + -4) + -2(x + 5)

Reorder the terms:
-33 + 9x = (-4 + 5x) + -2(x + 5)

Remove parenthesis around (-4 + 5x)
-33 + 9x = -4 + 5x + -2(x + 5)

Reorder the terms:
-33 + 9x = -4 + 5x + -2(5 + x)
-33 + 9x = -4 + 5x + (5 * -2 + x * -2)
-33 + 9x = -4 + 5x + (-10 + -2x)

Reorder the terms:
-33 + 9x = -4 + -10 + 5x + -2x

Combine like terms: -4 + -10 = -14
-33 + 9x = -14 + 5x + -2x

Combine like terms: 5x + -2x = 3x
-33 + 9x = -14 + 3x

Solving
-33 + 9x = -14 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-33 + 9x + -3x = -14 + 3x + -3x

Combine like terms: 9x + -3x = 6x
-33 + 6x = -14 + 3x + -3x

Combine like terms: 3x + -3x = 0
-33 + 6x = -14 + 0
-33 + 6x = -14

Add '33' to each side of the equation.
-33 + 33 + 6x = -14 + 33

Combine like terms: -33 + 33 = 0
0 + 6x = -14 + 33
6x = -14 + 33

Combine like terms: -14 + 33 = 19
6x = 19

Divide each side by '6'.
x = 3.166666667

Simplifying
x = 3.166666667

See similar equations:

| 3(s+1)-(s-1)-(s-1)=4s+2 | | x(.33)+x+x+5=40 | | 8t^2-10=82 | | 7-(x+2)-4(1x+6)=2(x-3) | | 15/2-15y/7=15y/16 | | 9/6v=36 | | x+.33+x+x+5=40 | | 0=-16t^2-80t+1600 | | 5-(x+2)-4(7x+5)=2(x-5) | | x/x-2=8/3 | | (13/6)-(8x/6)=(27x/6)-(57/6) | | x(5*3)=30 | | 60+15x+5+22x+4=180 | | (9x-3)(5x+6)=0 | | G(t)=4t^2-3 | | 15a-7=9a+5 | | 7x+3=16x-4 | | 3/9-(5x)/9=2/9-(8x)/9 | | p^-8/q^-9 | | x^2-22x-85=0 | | x=165-2x | | (11/6)x=(11/12) | | 5ln(x+3.5)=4.5 | | 2(3)x=12 | | -2y-12=2(v+2) | | -8=12e-20 | | S^2-2s-3=0 | | 10-2j=5-3j | | log2/log1.03 | | 4x(3x^2-1)=25x^2+40x+16 | | -ay-9=15 | | 2(13)=41+x |

Equations solver categories